Paving the way toward the world's first 200mm SiC pilot line. (15th November 2021) - Musolino, Mattia; Xu, Xueping; Wang, Hui; Rengarajan, Varathajan; Zwieback, Ilya; Ruland, Gary; Crippa, Danilo; Mauceri, Marco; Calabretta, Michele; Messina, Angelo
Abstract: In recent years, the power electronics industry based on silicon carbide (SiC) has rapidly expanded, but suppliers are struggling to meet the market demand both for final devices and for the starting raw material, which nowadays consists of SiC wafers with a diameter of 150 mm (6 inches). For this reason, the top industrial players in the field of SiC power electronics are starting the development of next-generation wafers with a diameter of 200 mm (8 inches). This work describes the recent achievements in the implementation of the world's first industrial pilot line to produce power devices based on 200 mm SiC wafers. In particular, the crystal growth of the 200 mm SiC boules, the slicing and polishing of the wafers, the deposition of the epitaxial layer, and the first tests in the pilot lines are presented.